2018
DOI: 10.1177/1010428318780859
|View full text |Cite
|
Sign up to set email alerts
|

Decreased expression of cell adhesion genes in cancer stem-like cells isolated from primary oral squamous cell carcinomas

Abstract: The goal of this study was to isolate cancer stem-like cells marked by high expression of CD44, a putative cancer stem cell marker, from primary oral squamous cell carcinomas and identify distinctive gene expression patterns in these cells. From 1 October 2013 to 4 September 2015, 76 stage III-IV primary oral squamous cell carcinoma of the gingivobuccal sulcus were resected. In all, 13 tumours were analysed by immunohistochemistry to visualise CD44-expressing cells. Expression of CD44 within The Cancer Genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 59 publications
(72 reference statements)
0
6
0
Order By: Relevance
“…The primary reason for testing CD44 in HNSC was that it had been previously used successfully to mark CSCs in another epithelial tissue, e.g., breast tumors (3, 4). There was also evidence from immunohistochemistry of head and neck tumor sections that CD44 stained only the basal or poorly differentiated tumor cells, and its staining pattern was mutually exclusive to that of involucrin, a well-known terminal differentiation marker in these epithelia (5,21). Although this has been corroborated by more recent studies, ambiguities have persisted (22).…”
Section: Isolation Of Cscs From Oral Cancers Using the Cell Surface Marker Cd44mentioning
confidence: 94%
See 3 more Smart Citations
“…The primary reason for testing CD44 in HNSC was that it had been previously used successfully to mark CSCs in another epithelial tissue, e.g., breast tumors (3, 4). There was also evidence from immunohistochemistry of head and neck tumor sections that CD44 stained only the basal or poorly differentiated tumor cells, and its staining pattern was mutually exclusive to that of involucrin, a well-known terminal differentiation marker in these epithelia (5,21). Although this has been corroborated by more recent studies, ambiguities have persisted (22).…”
Section: Isolation Of Cscs From Oral Cancers Using the Cell Surface Marker Cd44mentioning
confidence: 94%
“…CD44 is widely expressed on the surface of hematopoietic cells, and head and neck cancers are typically wellinfiltrated by immune cells. In fact, studies that have reported FACS profiles of cells from primary patient HNSCs have estimated the percentage of mature lineage marker-positive or Lin + cells (includes hematopoietic and stromal cell populations) to be as high as 50-60% in many tumors (21,24). There are two consequences to this observation-1.…”
Section: Isolation Of Cscs From Oral Cancers Using the Cell Surface Marker Cd44mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, BE-43547A2, which belongs to the naturally occurring cyclic depsipeptides, can selectively target pancreatic CSCs 178 . Researcher have also found several naturally derived compounds that can ablate CSCs in melanoma more effectively 177 . In addition, curcumin, a natural product extracted from Curcuma longa plants, can suppress stemness of HNSCC CSCs through inhibition of RXRα 178 …”
Section: Clinical and Therapeutic Implications Of Hnscc Cscsmentioning
confidence: 99%